Protective role of magnesium in the neutralization by antibodies of Chlamydia trachomatis infectivity. - Peterson, E M (1988)
Neutralization of the infectivity of Chlamydia trachomatis was assessed by using polyclonal antisera and monoclonal antibodies (MAbs). Polyclonal antisera and a species-reactive MAb as well as a subspecies-specific MAb, both of which were directed toward the major outer membrane protein of C. trachomatis, reduced the number of chlamydial inclusion-forming units in an in vitro assay. Neutralization was dependent on the presence of complement. The species-specific MAb reacted with all 15 serovars by a microimmunofluorescence assay and a dot blot enzyme-linked immunosorbent assay with heat-treated elementary bodies. On the other hand, this same MAb reacted with all serovars, except those in the C complex, by the dot blot enzyme-linked immunosorbent assay with viable organisms and neutralized in vitro all 10 serovars tested, except those in the C complex. When neutralization assays were performed in a solution containing Mg2+, neutralization by both polyclonal antisera and MAbs was significantly reduced. A dose response to Mg2+ supplied as MgSO4 revealed that all concentrations tested from 50 to 800 microM had some effect. Concentrations of greater than or equal to 400 microM MgSO4 completely abolished neutralization at the lowest dilution of polyclonal antisera and species-reactive MAb tested. Although Mg2+ also blocked the neutralization effect of the subspecies-specific MAb, this neutralization was not as complete as that observed with the species-reactive MAb. Addition of Mg2+ to the assay over the initial 45 min of incubation of C. trachomatis with MAb and complement showed that the organisms could be rescued to some extent over the first 30 min of incubation, after which time neutralization of infectivity could not be reversed. C. trachomatis treated with Mg2+, the species-reactive MAb, and complement were lethal to mice in an in vivo toxicity and infectivity assay, whereas mice injected with organisms incubated with the same MAb and complement without Mg2+ survived.